Measuring the effectiveness of financial management applications in fostering financial transparency and accountability within educational organizations - Sihombing, Denny Jean Cross (Jurnal Info Sains : Informatika dan Sains, 2024)
Financial management in educational organizations faces complex challenges related to managing limited financial resources. Transparency and financial accountability are the primary focus in maintaining the integrity of educational organizations. This research employs qualitative and quantitative approaches to understand the role of financial management applications in enhancing financial transparency and accountability in educational organizations. The study reveals various challenges, successes, and barriers associated with using such applications through in-depth interviews and statistical analysis. The findings indicate a significant improvement in the level of financial transparency and accountability following the implementation of the application, although some obstacles still need to be addressed. The contribution lies in providing a deeper understanding of the effectiveness of financial management applications in enhancing financial transparency and accountability in educational environments, as well as offering practical recommendations for practitioners and policymakers in educational financial management.